Demonstrating behavioural soft robotics to light source - Baharudin, Bahadurhisham; Sulaiman, Nasri; Md Yunus, Nurul Amziah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Recently Soft Robotics as a new development in Robotics technology having rapidly grows globally. Intense to challenge in industry a lot of effort to produce in various ways to make Soft Robotics can adapt in any task and environment. Soft Robotics applied for many of purposes such as surgery, healthcare devices, search and rescue device, space instrument repair and mine detection. This new technology is a combination of advances in biomedical engineering, biomechanics, mathematical modeling, biopolymer chemistry and computer science.